Música e políticas socioculturais: a contribuição do canto coral para a inclusão social - Rita de Cássia Fucci Amato (Opus, 2009)
The aim of this paper is to discuss the relevance of choral singing for projects of social inclusion. It presents and analyzes philosophically and historically the social role of singing together, highlighting the thoughts of philosophers as Plato, Aristotle and Rousseau; it also analyzes sociologically the potentialities of choirs for the socio-cultural inclusion of underprivileged communities – introducing concepts and reflections by Pierre Bourdieu, Domenico de Masi and Paulo Freire – and studies multiple cases of successful projects of inclusive choral singing in several regions of Brazil. Finally, it presents a model-proposal of an inclusive project (Pro-InCanto - Program of Social Inclusion through Choral Singing), which can be adapted to the different realities and social contexts of the country. The article concludes that there is a great social potential of choral singing yet to be explored.